Customary Violations and Sanctions: A Comparative Study of Two Indigenous Communities in Bali and South Sulawesi - Ni Wayan Sartini; Sarkawi B. Husain; Salimulloh Tegar Sanubarianto; William Bradley Horton (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This comparative study examines how customary sanctions are applied in response to traditional law violations in Tenganan Pegringsingan (Bali) and Kajang Tanah Towa (South Sulawesi), and how these sanctions sustain ecological balance and social harmony. The research was conducted using in-depth interviews and participatory observation. Various types of sanctions are regulated by written and unwritten rules (traditional written customary law) of Tenganan Pegringsingan, including dosen, penging, sikang, sapa sumaba, and kesah. Meanwhile, in the Kajang Tanah Towa indigenous community, violations of the pasang (oral customary guidelines) are met with mild to severe sanctions. Serious violations are punished with poko’ ba’bala (base of the whip – for severe violations), tangnga ba’bala (middle of the whip – for moderate violations), and cappa ba’bala (tip of the whip – for minor violations). This study contributes to a deeper understanding of how indigenous legal systems function as effective mechanisms for environmental governance and community resilience.